PARADIGMA KONTEMPORER EKONOMI ISLAM (Muh. Abdul Mannan versus Syed Nawab Haedir Naqvi) - Yusuf, Asdar (State Institute of Islamic Studies (IAIN) Palu, 2014)
The Islamic economic paradigm calls more the attention when the contemporary world encourages the emergence of various kinds of thoughts, ideas, concepts. universality, productivity, reality, creativity, and even morality. Nevertheless, some of the basic assumptions of the core conception of the paradigm begins to be questioned. The problems are no more related to the perception of the mind, the ideas and the final product, but has covered the basic assumption about human nature, motivation, and effort, which became the basis of the economic assumption in which the agents work. This paper presents the overview of Muh. Abdul Mannan versus Syed Nawab Haedir Naqvi in three aspects of the study: the interpretation of some economic terms and concepts in the Quran and Sunnah, the approach employed in building theory and Islamic economic system as well as their views on the interpretation of the Islamic economic system.Kata kunci: Ekonomi Islam, Muh. Abdul Mannan, Nawab Haedir Naqvi